Human factors of fire and explosion accidents in petrochemical enterprises. Issue 4 (19th February 2019) - Chen, Mengmeng; Wang, Kai; Guo, Haijun; Yuan, Yingfeng
Abstract : Human factor is one of main causes of fire and explosion accidents in petrochemical enterprises. In order to minimize the accident frequency and associated damage, a better understanding of the role played by human factor in such accident is prerequisite. In the present study, 212 accidents are collected and analyzed. The Human Factors Analysis and Classification System‐Petrochemical Enterprise Fire and Explosion (HFACS‐PEFE) is established to examine the mechanism of human failure. The model indicates violations, intellectual limitations, inadequate supervision, and insufficient safety culture are the most important factors in causing fire and explosion accidents. Relationships between different human factors, which are involved in the HFACS‐PEFE framework, are identified by conducting chi‐square test and odds ratio (OR) analysis. Five accident development routes and corresponding probabilities are achieved. The route comprised of insufficient safety culture → inadequate supervision → intellectual limitations → violations is the easiest way to result in fire and explosion accidents. To avoid the occurrence of such accidents, direct and indirect measures are proposed to improve human performance. © 2019 American Institute of Chemical Engineers Process Saf Prog: e12043 2019